Sustainability assessment of the replacement of clay brick walls with in-situ composite sandwich walls - Lawania, Krishna; Lloyd, Natalie; Biswas, Wahidul (ISEC Press, 2014)
Clay bricks are used for house construction in Western Australia. Clay bricks produce large amounts of construction and demolition waste, and have a large carbon footprint. In order to achieve energy savings and greenhouse gas (GHG) reduction targets, there is a need to use an alternative wall system. The objective of this paper is to undertake a sustainability assessment of the replacement of clay brick walls with in-situ composite sandwich walls (CSW). A Life Cycle Assessment (LCA) tool has been applied to assess the carbon footprint and embodied energy consumption for non-insulated and insulated brick and CSW. The LCA analysis identified the stages or inputs/process causing the most significant impacts for determining further improvement opportunities. The findings indicate that a significant GHG reduction and energy saving can be achieved.